Chemotherapy for advanced non-pancreatic well-differentiated neuroendocrine tumours of the gastrointestinal tract, a systematic review and meta-analysis: A lost cause?. (March 2016) - Lamarca, Angela; Elliott, Emma; Barriuso, Jorge; Backen, Alison; McNamara, Mairéad G.; Hubner, Richard; Valle, Juan W.
Highlights: Limited systemic treatment options are available for non-pNETs: SSAs and IFN. Chemotherapy is believed to have limited activity in well-differentiated non-pNETs. Twenty studies were included (small, heterogeneous), thus limiting conclusions. Chemotherapy (alkylating agents + 5-FU/capecitabine) appears active in non-pNETs. Prospective studies addressing NET-related therapeutic challenges are required. Abstract: Background: Chemotherapy is well-established in the treatment of patients with well-differentiated neuroendocrine tumours (NETs) arising from the pancreas (pNETs); however, its role in patients with gastrointestinal non-pancreatic NETs (non-pNETs) is uncertain. This systematic review assesses the evidence for the role of chemotherapy in well-differentiated non-pNET patients. Methods: Eligible studies (identified using MEDLINE) were those reporting response and/or survival data for patients with well-differentiated non-pNETs receiving systemic chemotherapy. The primary end-point was overall-response (OR) rate; secondary end-points were progression-free survival (PFS), overall survival (OS), disease-stabilization (DS) and disease-control (DC) rates. Results: Of 6434 studies screened, 20 were eligible: one randomised phase III trial, 2 randomised phase II studies, 10 single-arm phase II trials and 7 retrospective analyses including a total of 264 patients (median of 11 patients per study, range 6–49); and employing multiple chemotherapy schedules. The mean "median PFS" and "median OS" were 16.9 months (95%-confidence interval (CI) 3.8–30.04) and 32.2 months (95%-CI 10.4–54.2), respectively. The non-weighted mean OR, DS and DC rates were 11.5% (95%-CI 5.8–17.2), 56.5% (95%-CI 38.1–74.9) and 70.7% (95%-CI 54.9–86.5), respectively. In studies including both pNETs and non-pNET patients, meta-analysis showed a lower OR-rate in the non-pNET patients when compared to pNETs [odds ratio (OR) 0.35 (95% CI 0.18–0.66)]; however significance was lost when high-risk bias studies were excluded in a sensitivity analysis [OR 0.45 (95% CI 0.19–1.07); p -value 0.07]. Conclusion: Studies were of evidence level-C with heterogeneous populations and treatments; and small patient numbers. Well-designed, prospective studies are needed to adequately evaluate the role of chemotherapy in this setting.